Number of Levels of Spinal Fusion Associated with the Rate of Joint-Space Narrowing in the Hip. (2nd June 2021) - Kawai, Toshiyuki; Shimizu, Takayoshi; Goto, Koji; Kuroda, Yutaka; Okuzu, Yaichiro; Fujibayashi, Shunsuke; Matsuda, Shuichi
Abstract : Background: Fusion of a joint reportedly increases force in the adjacent joints and leads to progression of arthritis. Whether lumbar spinal fusion increases force in the hip joint and promotes wear of the joint space is unclear. The purpose of this study was to evaluate the rate of joint-space narrowing in the hip following spinal fusion and to examine the effects of the number of levels fused on the joint-narrowing rate. Methods: We retrospectively reviewed data for patients who underwent lumbar spinal fusion from 2011 to 2018 at our institute. Patients with a previous hip surgery, Kellgren-Lawrence grade ≥II hip osteoarthritis, hip dysplasia, and rheumatoid arthritis were excluded. The rate of joint-space narrowing in the hip was measured in 205 eligible patients (410 hips) following spinal fusion, and the effects of sex, age, body mass index, indication for spinal fusion, laterality, sacral fixation, and number of levels fused on the narrowing rate were examined. Results: The rate of joint-space narrowing for all patients was 0.114 ± 0.168 mm/year. The narrowing rate for single-level fusion was 0.062 ± 0.087 mm/year, whereas that for fusion of ≥7 levels was 0.307 ± 0.254 mm/year. In the multivariate regression analysis, only the length of fusion (standardized coefficient [SC] = 0.374, p < 0.0001) was associated with an increased narrowing rate. When the narrowing rate was normalized by height, female sex was another risk factor for increased narrowing (SC = 0.109, p = 0.023). Secondary regression modeling performed with patients who underwent spinal fusion for degenerative disc disease showed that the length of fusion (SC = 0.454, p < 0.0001) and female sex (SC = 0.138, p = 0.033) were associated with increased joint-space narrowing. Conclusions: Longer spinal fusion was associated with the progression of hip joint narrowing following spinal fusion. Surgeons should be aware of the possible increased risk of hip degeneration following spinal fusion and should inform patients of this risk. Level of Evidence: Level III . See Instructions for Authors for a complete description of levels of evidence.